Drug abuse in Teenagers - Sravanthi Gandu; Shivathmika.B; Swetha.G (International Journal of Toxins and Toxics, 2024)
Teenage drug abuse is a significant public health concerns with far - reaching consequences. This abstract provides on overview of the prevalence, contributing Factor and consequences of drug abuse among adolescents. Drug abuse remains persistence and multifaceted issue globally, affecting individual’s families and society. Factors that influence the teenagers to experiment with drugs, including peer pressure, family dynamics and predisposition. The abstract also describes the various substance abused by teenagers, such as alcohol, marijuana, prescription medication and illicit drugs, highlighting their short term and long-term effect on physical and mental health. Additionally, it outlines evidence-based prevention and intervention strategies aimed at addressing teenage drugs abuse, emphasizing the importance of early identification, education and support. By understanding complexities drug abuse and implementing drug invention, communities work towards mitigating tits adverse effects and promoting the wellbeing of adolescents. Pharmacy plays an important role in addressing teenagers drug abuse through education, screening, intervention and referral services. This Focus on the role of pharmacies in treatment and prevention . Pharmacist can educate adolescent and their patients about the risk of drug abuse; proper medication uses and healthy. They can also conduct screening assignment to identify at risk individuals and provide intervention and naloxone dispensing for opioid overdose prevention. Collaboration with schools, healthcare providers and community organization are essential to comprehensive prevent and treatment program targeting teenagers. This include promoting parental involvement, implementing social based prevention, offering youth friendly services and expanding access of substance abuse treatment and harm reduction services.
Keywords: Teenagers; alcohol; marijuana; prescription medication and illicit drugs